Pathological changes in palatine tonsils of slaughtered water buffaloes (Bubalus bubalis) - Maria A.S. Teixeira; Márcio A.O. Moura; Gerson B.E. González; Claudina R.S. Pires; Tiago F.S. Santos; Gabriela Riet-Correa; Valíria D. Cerqueira; Pedro S. Bezerra Júnior (Pesquisa Veterinária Brasileira, 2024)
ABSTRACT: This study evaluated palatine tonsils from 327 water buffaloes collected in a slaughterhouse located in the city of Belém, Pará State, Brazil, over four months (nine sample collecting visits). The overwhelming majority (84.71%) of these buffaloes came from Marajó Island, Pará State, Brazil. The main pathological findings were crypt dilatations/keratin cysts (96.0%, 314 cases), mild to moderate follicular lymphoid hyperplasia (93.0%, 304 cases), crypt abscesses (79.8%, 261 cases), tonsillar corpuscles (31.2%, 102 cases) and tuberculoid granulomas (1.53%, 5 cases). Acid-fast bacilli (AFB) were observed in 20% (1 out of 5 cases) of these granulomas. The study indicates that pathological evaluation of tonsils in buffaloes can provide details of structural features of the organ in the species and information on subclinical or asymptomatic tonsillitis.